Analisis Strategi Pengembangan Usaha Produk Cokelat Almond Pada Kewirausahaan Mahasiswa - Alisia Mandasari; Fransisca Eka N; Amin Sadiqin (CV ODIS, 2023)
The development of a business is a way to improve, upgrade and implement a quality product from the company in progress. The purpose of product development is to maximize the achievement of product sales and also to increase customer satisfaction with these products. Many ways can be used to develop a business on a small scale. One of the product development efforts from the student activity program is made from chocolate and almonds. Chocolate is a processed product that many people like, so the demand for this chocolate product will continue to increase, and the existence of processed products made from chocolate will have a very positive impact on the income of small businesses in entrepreneurship. The purpose of this study is to analyze the development strategy and business position in economic life per sector. The research methodology used is qualitative, with data processing and analysis consisting of primary data analysis in the form of interview data and secondary data in the form of information about Chocolate Almond products. The research results show that the development of a chocolate-based business must be able to innovate according to consumer needs and expand market networks using market share strategies and market access strategies by increasing production volume through additional capital and utilizing modern technology networks